Antibacterial Potency of Jackfruit Leaf Extract (Artocarpus heterophyllus L.) Against Salmonella typhi - Mawardika, Herlinda; Wahyuni, Dwi; Khasanah, Siti Ma’rifatul (Universitas Muhammadiyah Surakarta, 2023)
Typhoid fever is a chronic disease caused by S. typhi bacterium. This disease can be transmitted via contaminated water or food, and close contact with an infected person. The symptomps of typhoid fever include high fever, stomach pain, headache, and constipation. Jackfruit (Artocarpus heterophyllus L.) leaves extract contain active compounds with antibacterial activity. This research aims to determine the inhibitory activity of jackfruit leaves extract against S. typhi. Jackfruit leaves were extracted by maceration using 70% ethanol as solvent. After that, organoleptic test, ethanol-free test and phytochemical screening of extract were carried out. Inhibitory activity of extract was conducted using well diffusion method, followed by determination of MIC and MBC. The results showed that jackfruit leaves extract contained flavonoid, tannins, saponin, and triterpenoid. Inhbitory activity of extract was found at concentration 20% (5.24 mm), 40% (6.78 mm), and concentration 60% (8.08 mm). The MIC value of extract was 12.5%. while the MBC could not be found. According to the results, ethanol extract of jackfruit leaves (70%) have potential compounds to inhibit the growth of S. typhi